High levels of exfoliated fragments following glycocalyx destruction in hemorrhagic fever with the renal syndrome are associated with mortality risk - Du, Hong; Hu, Haifeng; Li, Jing; Wang, Xiaoyan; Jiang, Hong; Lian, Jianqi; Zhang, Ying; Wang, Pingzhong (Frontiers in Medicine, 2023)
Background: The glycocalyx is a gel-like structure covering the luminal side of vascular endothelial cells and plays an important role in maintaining the integrity of the vascular endothelial barrier structure. However, the presence or absence of glycocalyx destruction in hemorrhagic fever with renal syndrome (HFRS) and its specific mechanism and role are still unclear. Methods: In this study, the levels of exfoliated glycocalyx fragments, namely heparan sulfate (HS), hyaluronic acid (HA), and chondroitin sulfate (CS) in HFRS patients were detected and their clinical application value on evaluation of disease severity and prognosis prediction were investigated. Results: The expression of exfoliated glycocalyx fragments in plasma was significantly increased during the acute stage of HFRS. The levels of HS, HA, and CS in patients during the acute stage were significantly higher than the healthy controls and the convalescent stage of the same type. HS and CS during the acute stage were gradually increased with the aggravation of HFRS, both of which presented significant association with disease severity. In addition, exfoliated glycocalyx fragments (especially HS and CS) demonstrated significant correlation with conventional laboratory parameters and hospitalization days. High levels of HS and CS during the acute phase were significantly associated with patient mortality and demonstrated obvious predictive value for the mortality risk of HFRS. Conclusions: The destruction and shedding of the glycocalyx may be closely associated with the endothelial hyperpermeability and microvascular leakage in HFRS. The dynamic detection of the exfoliated glycocalyx fragments may be beneficial for the evaluation of disease severity and prognosis prediction in HFRS.